Presence of phosphoric precursors of phospholipids in human placenta (Revista Española de Fisiología, 1959)
1. Deproteinized aqueous extracts of human placenta have been examined by column chromatography with Zeo-Karb 225,4.5 % cross linked, Na+ form. The more acidic components have been studied. 2. Glycerylphosphorylethanolamine, glycerylphosphorylcholine, phosphorylethanolamine and phosphorylcholine were isolated and determined. The presence of phosphorylserine is uncertain. Other amino-compounds were also identified and determined. Minor peaks were also found, but not identified. A peptide-like substance, containing phosphorous, has also been found. 3. The results are related to the problem of phospholipidphosphoric esters and phospholipid biosynthesis in the placenta.